Epidermoid Cyst of the Ear Lobule in Adult - Karmacharya, S.; Sah, S. K.; Adhikari, S. (Kathmandu University Medical Journal, 2021)
An epidermoid cyst is one of the most common benign cysts of the skin. The cyst is filled with keratin flakes and its wall is composed of keratinized, stratified, squamous epithelium. Epidermoid cysts can occur anywhere on the body, usually along the lines of embryonic fusion and mostly on the face, scalp, neck, chest, and upper back. Around 80% of the epidermoid cysts are seen in ovaries and testicles whereas, in the head and neck, they account for only about 7% and 1.6% of epidermoid cysts are reported in the oral cavity. The condition can be congenital or acquired. Congenital causes are rare and may be caused by the entrapment of ectodermal elements intradermally or subcutaneously during embryogenesis. Acquired causes of an epidermoid cyst may result from traumatic or iatrogenic implantation of epithelial cells into the dermal layer or from obstruction of a pilosebaceous unit in the hair follicle. Surgical excision completes the treatment.